2014
DOI: 10.1016/j.yjmcc.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic receptor-mediated transactivation of epidermal growth factor receptor decreases cardiomyocyte apoptosis through differential subcellular activation of ERK1/2 and Akt

Abstract: Rationale β-adrenergic receptor (βAR)-mediated transactivation of epidermal growth factor receptor (EGFR) has been shown to relay pro-survival effects via unknown mechanisms. Objective We hypothesized that acute βAR-mediated EGFR transactivation in the heart promotes differential subcellular activation of ERK1/2 and Akt, promoting cell survival through modulation of apoptosis. Methods and Results C57BL/6 mice underwent acute i.p. injection with isoproterenol (ISO) ± AG 1478 (EGFR antagonist) to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 86 publications
(94 reference statements)
2
45
0
Order By: Relevance
“…(Benter et al, 2004). Studies examining the injurious effects of ErbB1 or ErbB2 inhibition/deletion also support involvement of ROS generation, mitochondrial channels and PKC (Gordon et al, 2009), and modulation of caspase-3 and pro-and anti-apoptotic Bcl proteins and JNK activity (Grazette et al, 2004;Uetani et al, 2009;Grisanti et al, 2014). The precise roles of these mediators in cardiac protection awaits further analysis.…”
Section: Role In Adaptive Protection -Ischaemic Preconditioningmentioning
confidence: 86%
See 3 more Smart Citations
“…(Benter et al, 2004). Studies examining the injurious effects of ErbB1 or ErbB2 inhibition/deletion also support involvement of ROS generation, mitochondrial channels and PKC (Gordon et al, 2009), and modulation of caspase-3 and pro-and anti-apoptotic Bcl proteins and JNK activity (Grazette et al, 2004;Uetani et al, 2009;Grisanti et al, 2014). The precise roles of these mediators in cardiac protection awaits further analysis.…”
Section: Role In Adaptive Protection -Ischaemic Preconditioningmentioning
confidence: 86%
“…In cardiac cells, EGFR transactivation has been linked to angiotensin (Rakesh et al, 2010), muscarinic (Krieg et al, 2002;Krieg et al, 2004;Miao et al, 2015), endothelin (Kodama et al, 2002;Chen et al, 2006), opioid (Cao et al, 2005;Cohen et al, 2007;Forster et al, 2007;Zhang et al, 2015), bradykinin (Methner et al, 2009), adrenergic (Noma et al, 2007;Grisanti et al, 2014), adenosine (Williams-Pritchard et al, 2011), and sphoingosine-1 phosphate (S1P) (Hofmann et al, 2009) GPCRs, with transactivation via angiotensin II (Ang II) perhaps the most well studied. Several Gq-linked receptors (Ang II, ET-1, -ARs) may promote cardiac hypertrophy/remodelling, whereas transactivation by adenosine, opioid, bradykinin or muscarinic receptors may be protective, enhancing cell survival.…”
Section: Mechanisms Of Egfr Transactivationmentioning
confidence: 99%
See 2 more Smart Citations
“…In cardiomyocytes, Nur77 expression can be induced by ischemia/reperfusion injury, and translocation of Nur77 to the mitochondria mediates cardiomyocyte apoptosis in response to oxidative stress (19). Interestingly, a recent report demonstrated that the expression of Nur77 in the heart was rapidly induced in vivo following ␤-adrenergic stimulation (20,21). However, at this time, the exact functional significance of Nur77 in the heart remains unknown.…”
mentioning
confidence: 99%